The Hospitality Stakeholders’ Perception toward Industry and Education Relationship: Strategies for Effective Curriculum Design - Srisangkaew, Kulrisa (Connexion: Journal of Humanities and Social Sciences, 2022)
This qualitative research aims to investigate the perception of hospitality stakeholders view toward the existing relationship between hospitality education and the industry in Bangkok, and to propose strategies in order to reduce the gaps within and among the hospitality stakeholders for more effective curriculum design. This study employed in-depth, semi-structured interviews, which were conducted with a sample of 5 hospitality educators, 5 hospitality managers, and 5 hospitality undergraduate intern students, in a total of 15 respondents. For the sampling method, a non-random purposive sampling technique was used with hospitality educators from the participating universities and colleges deemed to have the strongest qualifications, expertise, and knowledge required for the research. From the interview result, it was found that there are links between the hospitality industry and education. This implies that there is a need to incorporate all three stakeholders to establish quality relationships between the hospitality industry and education. Moreover, the findings indicate that the success of students depends on the curriculum content which prepares them for the real industry with effective training programs. To ensure survival, therefore, the curriculum designers need to meet the needs of the industry to have a core discipline, which can be achieved by more practical skills training, more case-study work based on the world of hospitality, and by industry representatives being closely involved in all aspects of course development.